ALGORITME TEHNOLOGICAL PROCESE KEYBOARD STRAW- SHAKER - V.I. ZUBKOV (Advanced Engineering Research, 2009)
The theory keyboard straw-shaker is consideredexamined in view of elastic - viscous behaviour of straw in interaction with a surface of a key. The theory straw-shaker is stated in the form of the description of algorithm of technological process of work keyboard straw-shaker without a substantiation and a conclusion of used formulas with references to sources in which substantiations of these formulas are given. Results of numerical experiments for dry and damp lots of a winter wheat and barley as corresponding schedules are resulted.